Ensino-aprendizagem da função quadrática usando o Geogebra - SOUSA, Luciane dos Santos (2022)
Education has undergone major methodological changes that are identified as teaching trends. Among these, the use of Information and Communication Technologies stands out, adopting educational softwares that enhance visualization and experimentation in the construction of mathematical concepts. But for this it is necessary to choose suitable software and a methodology capable of taking advantage of the positive characteristics of the computer. The present work has as its theme “Teaching-Learning the Quadratic Function Using Geogebra”, and as a general objective to know if the Geogebra Software facilitates students' learning about the quadratic function and its graphs. For this, a bibliographical basis was developed by different authors in the area of information technology and on Geogebra, in addition to a field research making a qualitative descriptive analysis. In this way, see if the use of the GeoGebra software can represent an important methodology for the teaching-learning of the quadratic function and its graphs, enabling students to have a meaningful and interesting learning, which leads them to understand mathematical concepts.